Effect of Co on morphology and preparation of in situ synthesis of WC-Co composite powders. (8th May 2019) - Zhu, ErTao; Zhang, JiuXing; Guo, ShengDa; Yang, XinYu; Zhang, Xiang; Yang, JianGao
Abstract: The WC and WC-Co composite powders were fabricated through spray-drying, calcinations as well as by reduction and carbonization treatment using the precursors, AMT, C6 H12 O6, Co(CH3 COO)2  · 4H2 O and H2 O with different Co content (0, 4, 6, 8, 12 wt%). The results show that the obtained WC by the spray-drying method were nearly spherical with a smooth surface and maintaining the spherical structure of AMT. Also, the loose cobalt oxide powders prepared by the calcinations of precursors had uniform structures with good dispersivity, and higher degree of sphericity when Co content was greater than 6 wt%. Moreover, aggregates with original sheet structure exist in the WC and WC composite powders prepared by reduction and carbonization, and also higher the Co content, the more obvious the agglomeration. Using XRD, EDS and XPS, activated carbon, WO3 and Co3 O4 with a small content of WC were detected during the pretreatment of calcined products. Furthermore, the preparation temperature of pure WC powders was relatively high (about 1200 °C) compared to those contained with Co. The preparation temperature of WC-Co composite powders gradually decreased with an increase in the Co content. When the Co content increased to 12 wt%, the temperatures for reduction and carbonation remained at 1050 °C.